Body image, visual working memory and visual mental imagery - Darling, Stephen; Uytman, Clare; Allen, Richard J; Havelka, Jelena; Pearson, David G (PeerJ PrePrints, 2014)
Body dissatisfaction (BD) is a highly prevalent feature amongst females in society, with the majority of individuals regarding themselves to be overweight compared to their personal ideal, and very few self-describing as underweight. To date, explanations of this dramatic pattern have centred on extrinsic social and media factors, or intrinsic factors connected to individuals’ knowledge and belief structures regarding eating and body shape, with little research examining links between BD and basic cognitive mechanisms. This paper reports a correlational study in which visual and executive cognitive processes that could potentially impact on BD were assessed. Visual memory span and self-rated visual imagery were found to be predictive of BD, alongside a measure of inhibition derived from the Stroop task. In contrast, spatial memory and global precedence were not related to BD. Results are interpreted with reference to the influential multi-component model of working memory.
Keywords: Body dissatisfaction; Body image; Visual imagery; visual memory; working memory